Factors that contribute to loss to follow-up in the medium term after initiation of anti-vascular endothelial growth factor therapy for neovascular age-related macular degeneration in Japanese patients - Takaaki Sugisawa; Fumi Gomi; Yuri Harada; Hiroko Imaizumi; Shuichiro Aoki; Akiko Miki; Maya Kishi; Tomofusa Yamauchi; Daisuke Nagasato; Yoko Ozawa; Masatoshi Haruta; Nobuhiro Kato; et al. (PLoS ONE, 2025)
Purpose To identify time-specific factors associated with loss to follow-up (LTFU) in the early to medium term after initiating anti-vascular endothelial growth factor (VEGF) treatment in patients with neovascular age-related macular degeneration (nAMD) in Japan. Methods The study had a retrospective multicenter case–control design and was performed across 16 specialist retinal facilities in Japan. Patients diagnosed with nAMD at their initial visit who initiated treatment between January 2017 and December 2020 were included. Patient characteristics were analyzed to identify factors associated with LTFU within 3 months (very early), 3 months to 1 year (early), and 1 year to 2 years (medium term) after starting treatment. Results Data for 2389 patients with nAMD were analyzed. The very early, early, and medium-term LTFU rates were 6.8%, 13.8%, and 21.2%, respectively. Stepwise regression analysis identified factors that were significantly associated with LTFU at a very early stage to be greater central retinal thickness at baseline and a prior treatment history, those associated with early LTFU to be worse baseline best-corrected visual acuity (BCVA), anti-VEGF treatment combined with photodynamic therapy, and a follow-up period that overlapped with the COVID-19 pandemic, and that associated with medium-term LTFU to be worse BCVA at 3 months. LTFU in any period within 3 months to 2 years was more likely in patients aged >80 years, and LTFU very early within 3 months was more likely in those aged <60 years. A poor baseline BCVA (logMAR) of >1 was a risk factor for LTFU within 3 months and 1 year, whereas LTFU was significantly less likely in patients with good baseline BCVA (<0.1). Conclusion The LTFU rate in patients with nAMD increased over time. Factors contributing to LTFU vary depending on the time since initiation of treatment.